2005
DOI: 10.1590/s1413-86702005000600002
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to an occupational blood borne pathogens exposure management program among healthcare workers and other groups at risk in Argentina

Abstract: We conducted a retrospective review of 130 occupational blood borne pathogens exposure (BBP-OE) records at Centro de Estudios Médicos e Investigaciones Clínicas, a university hospital with an ongoing educational program and a postexposure management program for healthcare workers (HCWs) since 1995, in order to evaluate adherence to a hospital BBP-OE management program. We compared HCWs from our institution (Group 1) and HCWs from independent institutions that contract our postexposure management program (Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 8 publications
0
7
0
3
Order By: Relevance
“…The frequency of HCV in Turkey varies between 1.2% and 4% [7]. Based on the risk of exposure to blood and body fluids (BBF), HBV and HCV infections constitute a well-recognized occupational risk for healthcare workers (HCWs) [8][9][10][11][12]. According to the WHO reports, each year approximately three million of the overall 35 million HCWs worldwide experience percutaneous exposure to blood-borne viruses (BBVs) resulting in 16 000 hepatitis C and 66 000 hepatitis B infections, mainly from low-income countries [13] where a combination of increased risk, fewer safety precautions and inadequate risk reduction strategies were evident [14].…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of HCV in Turkey varies between 1.2% and 4% [7]. Based on the risk of exposure to blood and body fluids (BBF), HBV and HCV infections constitute a well-recognized occupational risk for healthcare workers (HCWs) [8][9][10][11][12]. According to the WHO reports, each year approximately three million of the overall 35 million HCWs worldwide experience percutaneous exposure to blood-borne viruses (BBVs) resulting in 16 000 hepatitis C and 66 000 hepatitis B infections, mainly from low-income countries [13] where a combination of increased risk, fewer safety precautions and inadequate risk reduction strategies were evident [14].…”
Section: Introductionmentioning
confidence: 99%
“…Availability of information and resources was not enough to guarantee compliance of HCPs with PEP guidelines in Brazil. 9 The study by Kiertiburanakul and colleagues suggested that adverse effects of antiretroviral medications, such as gastrointestinal reactions, were frequent reasons for the discontinuation of therapy. 10 Therefore, the tolerability of PEP regimens among HCPs was poor, which in turn compromised treatment efficacy.…”
mentioning
confidence: 99%
“…This may be due in part to the finding that compared to other health care workers, nurses had the lowest compliance rates with standard procedures. Knowledge of the patient's seropositivity status did not seem to improve compliance rate (Miceli et al, 2005).…”
Section: Occupational Exposure and Seroconversionmentioning
confidence: 93%